2007
DOI: 10.1158/1055-9965.epi-07-0457
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Epidemiology and Biomarkers in Etiologic Cancer Research: The New in Light of the Old

Abstract: The purpose of this review is to evaluate progress in molecular epidemiology over the past 24 years in cancer etiology and prevention to draw lessons for future research incorporating the new generation of biomarkers. Molecular epidemiology was introduced in the study of cancer in the early 1980s, with the expectation that it would help overcome some major limitations of epidemiology and facilitate cancer prevention. The expectation was that biomarkers would improve exposure assessment, document early changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(82 citation statements)
references
References 89 publications
1
80
0
1
Order By: Relevance
“…Breast cancer displays a high heterogeneity in terms of etiology and histology as well as prognosis, metastatic evolution and response to treatments. Deciphering the molecular basis of such heterogeneity is a major challenge, now achievable through new bio-molecular and analytical techniques, aiming at a comprehensive cancer characterization for risk stratification, therapeutic target identification and appropriate treatment selection [2].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer displays a high heterogeneity in terms of etiology and histology as well as prognosis, metastatic evolution and response to treatments. Deciphering the molecular basis of such heterogeneity is a major challenge, now achievable through new bio-molecular and analytical techniques, aiming at a comprehensive cancer characterization for risk stratification, therapeutic target identification and appropriate treatment selection [2].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular epidemiological data for human cancers have been analyzed to establish causation, and several chemical carcinogen signatures have been identified [43][44][45][46]. However, only a limited number of controversial radiation signatures have been reported in human cancers, such as a p53 mutation in lung tumors of miners heavily exposed to radon [47] and a possible distinct pattern of RET oncogene rearrangement in post-Chernobyl thyroid tumors [48].…”
Section: Discussionmentioning
confidence: 99%
“…Elucidation of the mechanisms involved will aid in the identification of biomarkers of the exposure as well as biomarkers of the disease: these findings will in turn add weight to the association helping researchers assign causality. Vineis and Perera [50] propose the use of complementary study designs to establish new biomarkers that lie on the causal pathway between exposure and disease. For example, identification of biomarkers that in prospective studies are shown to be associated with adherence to the Mediterranean diet and evidence from nested case-control studies that these same biomarkers are predictive of breast cancer risk, will be sufficient to classify these biomarkers as part of the mechanistic pathway linking exposure to disease and to regard this association as causal (Figure 4).…”
Section: Investigating the Mediterranean Diet: Concepts Challenges mentioning
confidence: 99%